2020
DOI: 10.1063/5.0014142
|View full text |Cite
|
Sign up to set email alerts
|

Double excitation multi-stability and multi-pulse chaotic vibrations of a bistable asymmetric laminated composite square panels under foundation force

Abstract: The double excitation multi-stability and Shilnikov-type multi-pulse jumping chaotic vibrations are analyzed for the bistable asymmetric laminated composite square panel under foundation force for the first time. Based on the extended new high-dimensional Melnikov function, the explicit sufficient conditions are obtained for the existence of the Shilnikov-type multi-pulse jumping homoclinic orbits and chaotic vibrations in the bistable asymmetric laminated composite square panel, which implies that multi-pulse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…On the basis of the previous experimental research, Arrieta et al [32] established a non-smooth double-well dynamic model with the lateral displacement as the variable and the critical snapthrough displacement as the dividing point, and found that double-well dynamics of a bistable plate exhibited dynamic snapthrough motions and chaotic responses. Dynamic snapthrough motions and nonlinear vibrations of bistable unsymmetric composite laminates under the foundation excitation were studied [33,34]. Emam et al [35] investigated snapthrough motions of bistable orthogonal composite laminates under the concentrated moment, the normal force and the tangential force respectively.…”
Section: Introductionmentioning
confidence: 99%
“…On the basis of the previous experimental research, Arrieta et al [32] established a non-smooth double-well dynamic model with the lateral displacement as the variable and the critical snapthrough displacement as the dividing point, and found that double-well dynamics of a bistable plate exhibited dynamic snapthrough motions and chaotic responses. Dynamic snapthrough motions and nonlinear vibrations of bistable unsymmetric composite laminates under the foundation excitation were studied [33,34]. Emam et al [35] investigated snapthrough motions of bistable orthogonal composite laminates under the concentrated moment, the normal force and the tangential force respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Multipulse chaotic motions are very common in highdimensional systems. With the extended Melnikov method, Zhang et al [14] investigated multipulse jumping chaotic vibrations of the bistable asymmetric laminated composite square panel under foundation force. e energy-phase method [15][16][17][18][19], proposed by Haller, is a global perturbation method for analyzing multipulse chaotic motions of high-dimensional nonlinear systems.…”
Section: Introductionmentioning
confidence: 99%
“…They also verified the theoretical results with experiments. Zhang et al [57] predicted chaotic vibrations of a bi-stable asymmetric laminated composite square panel under foundation forces for the first time.…”
Section: Introductionmentioning
confidence: 99%